2009
DOI: 10.2105/ajph.2007.128702
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Physical and Social Neighborhood Environments on Children's Physical Activity and Obesity

Abstract: Our findings suggest that neighborhood social factors as well as the physical environment should be considered in the development of health policy and interventions to reduce childhood obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
198
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(210 citation statements)
references
References 58 publications
9
198
3
Order By: Relevance
“…Similar outcomes were found by Saelens et al (2003a, b), who showed that safer neighbourhoods with a mixture of functions often result in more physical activity and less overweight and obesity. Similarly depicted by the results of Franzini et al (2009), it seems that a favourable social environment of the neighbourhood positively influences overall physical activity.…”
Section: Discussionsupporting
confidence: 57%
“…Similar outcomes were found by Saelens et al (2003a, b), who showed that safer neighbourhoods with a mixture of functions often result in more physical activity and less overweight and obesity. Similarly depicted by the results of Franzini et al (2009), it seems that a favourable social environment of the neighbourhood positively influences overall physical activity.…”
Section: Discussionsupporting
confidence: 57%
“…95,96 Researchers have used various approaches to examine associations between BE factors and childhood obesity. [95][96][97][98][99][100][101][102][103][104][105][106][107][108] Evidence in the literature shows that improvements to the BE (e.g., places to exercise, green space, sidewalks, recreational areas, neighborhood safety, food access and healthier food options) will increase physical activity, potentially resulting in a decrease in obesity. 94,97,98,109 Decreased activity levels have been found when these services are difficult to access.…”
Section: Built Environmentmentioning
confidence: 99%
“…101 On the other hand, since children spend a lot of their time in school, they obtain physical activity by participating in teams, lessons, and gym class, suggesting that neighborhood physical characteristics such as traffic, density, and land use may be less relevant. 100 Neighborhood Food Outlets Many food outlets readily accessible to children have poor dietary choices (e.g., fast-food restaurants, convenience stores, small food stores) with high fat, large portion sizes, and sugary drink options. [111][112][113] Research shows that children who have easy access to poor quality food outlets tend to have a higher BMI and the potential to become overweight/obese when compared to children who do not have easy access to these food outlet types.…”
Section: Built Environmentmentioning
confidence: 99%
“…Moreover, past studies of the neighborhood environment and children’s PA have focused on the impact of the environment on total day PA (19, 23, 54); however, it is also important to understand the potential effects of this environment on PA across different times of the day (e.g., afterschool hours). Evidence suggests that the afterschool period (3:00 pm to 6:00 pm) is the time period when youth are most likely to participate in MVPA (2) and accumulate up to 50% of their total PA. (31, 49) Additionally, considering a large proportion of youth do not attend afterschool programs and likely return home (supervised or unsupervised) during the afterschool hours,(1) the neighborhood environment may exhibit a profound influence on MVPA behavior during this time period.…”
Section: Introductionmentioning
confidence: 99%